Profile of The Development of Interpersonal Intelligence for Class XI MIPA Students at SMA Negeri 1 Bungo Jambi Province - Febri Yadi Heri yanto, Heri; Zaini, Ahmad; Dianto, Mori (Lembaga Riset Mutiara Akbar, 2022)
This research is motivated by the fact that there are still students who are less able to relate socially with other people. Students' problems related to interpersonal intelligence, it can be seen that the behavior of students in class XI mipa SMA Negeri 1 Bungo has problems regarding interpersonal intelligence in general at school. The purpose of this study is to describe the development of interpersonal intelligence of students in class XI MIPA at SMA Negeri 1 Bumgo 1.) To reveal the interpersonal intelligence of students seen from social sensitivity. 2.) To reveal the interpersonal intelligence of students seen from social insight. 3.) To reveal the interpersonal intelligence of students seen from social communication. This type of research is descriptive quantitative, the research population of students in SMA Negeri 1 Bungo the sample to be carried out in the study is 133 students. The sample in this study is class XI MIPA by using random sampling technique. The results of the study on the Interpersonal Intelligence Development Profile of Students in Class XI Mipa SMA Negeri 1 Bungo Jambi Province seen from the identification results were generally in the very high range with a percentage of 60.90%. This means that many students have very high interpersonal intelligence in SMA Negeri 1 Bungo. Then interpersonal intelligence is divided into 3 indicators, namely: 1) interpersonal intelligence can be seen from social sensitivity is in the very high category 67.67%, 2) interpersonal intelligence can be seen from social insight is in the very high category 56.39%, 3) Interpersonal intelligence can be seen from social communication which is in the very high category of 60.15%. Based on the results of the study, it can be recommended to students in order to further improve interpersonal intelligence well